From Wetlands to the World: Internationalizing Banjar Folktales through a Digital English Learning Module - Listia, Rina; Eka Chandra, Noor; Shaunaa, Roaini; Ifadloh, Nur; Afifah; Syahrani, Hilal; Stefanus Hendrawan, Wahyu (SALEE: Study of Applied Linguistics and English Education, 2026)
This study investigates the development of an interactive e-module based on South Kalimantan folktales to enhance English language learning while internationalizing and preserving the local values of the Banjar tribe. Grounded in Hutchinson and Waters’ (1987) framework of needs analysis, data were collected through questionnaires distributed to high school students (n = 159). The analysis explored five dimensions: (1) the need for digital materials; (2) interest in folklore-based learning; (3) understanding of local wisdom; (4) the relevance of folktales to ELT; and (5) expectations for e-module design. Findings reveal that students strongly support the integration of folktales into digital materials, valuing interactive multimedia features, bilingual formats, and cultural reflections. The study highlights the potential of folklore-based digital resources not only to foster English proficiency but also to strengthen cultural identity and internationalize indigenous heritage. The implications suggest that digital pedagogy can serve as a bridge between global education and local wisdom, positioning cultural-based e-learning as a contemporary response to both educational and intercultural challenges.